Pengaruh Pembelajaran PQ4R Berbasis Microlearning terhadap Literasi Sains dan Hasil Belajar Biologi: Studi Kuasi-Eksperimen dengan Mengontrol Pengetahuan Awal - Andi Nurfaizah Yusuf; Firdaus Daud; Ismail; Rachmawaty; Faisal (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effect of implementing the PQ4R learning model assisted by video microlearning on students' scientific literacy and biology learning outcomes in the nervous system material. The study used a quantitative approach with a quasi-experimental nonequivalent control group design. The experimental class was taught using the PQ4R model assisted by video microlearning, while the control class used Project Based Learning (PjBL). Video microlearning was integrated in the Read and Reflect stages to help visualize abstract nervous system concepts. The study sample consisted of 36 students in the experimental class and 35 students in the control class. Data were analyzed using descriptive statistics and analysis of covariance (ANCOVA). The results showed that the average posttest of scientific literacy in the experimental class was 92.44, higher than the control class at 87.20. The average posttest of biology learning outcomes in the experimental class was 93.33, while the control class was 87.89. ANCOVA results showed that the learning model had a significant effect on scientific literacy (F = 29.282; p < 0.001; η² = 0.301) and biology learning outcomes (F = 26.082; p < 0.001; η² = 0.277) after initial abilities were controlled. The research findings showed that the PQ4R model assisted by microlearning videos was more effective than Project Based Learning (PjBL) in helping students understand the concept of the nervous system and improving scientific literacy and biology learning outcomes.